Pengaruh Struktur Modal Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Food And Beverages Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021–2023 - Nurulfa; Taufik, Haviz; Efrina, Liona (Pusat Riset dan Inovasi Nasional, 2026)
This study is motivated by the importance of capital structure in determining a company’s profitability. Capital structure, which is reflected by Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), is an important factor that can affect Return on Equity (ROE) as an indicator of financial performance. This study aims to analyze the effect of DER and DAR on ROE in food and beverages manufacturing companies listed on the Bursa Efek Indonesia during the period 2021–2023. The research method used is a quantitative method with a panel data approach. Data analysis techniques use panel data regression processed using EViews software. The model used in this study is the Fixed Effect Model (FEM) as the best model. The results show that partially DER has a negative and significant effect on ROE, while DAR has a positive and significant effect on ROE. Simultaneously, DER and DAR have a significant effect on ROE. This indicates that capital structure plays an important role in improving company profitability.